(NON-HUMAN)ANIMAL COMPANIONSHIP: A CRUCIAL SUPPORT FOR PEOPLE DURING THE COVID-19 PANDEMIC - HOY-GERLACH, JANET; RAUKTIS, MARY; NEWHILL, CHRISTINA (Society Register, 2020)
Background Human-animal interaction (HAI) offers benefits across physical, emotional, psychological, and social spheres of human functioning. The aim of this paper is to delineate how animal companionship, via provision of HAI benefits, offers vital support to people experiencing the COVID-19 pandemic and associated stressors. Method Each of the empirically supported types of HAI benefits – physical, emotional, psychological, and social – will be situated within a biopsychosocial framework of human functioning and considered in terms of how they may help to ameliorate stressors specifically related to the COVID-19 pandemic. Findings Benefits derived from animal companionship may help alleviate physical, emotional, psychological, and social stressors specifically related to experiencing the COVID-19 pandemic. Discussion Benefits of animal companionship may be particularly salient for well-being and coping when people are experiencing a dramatic increase in stressors via a pandemic crisis. Community responses need to include plans (pet food pantries, temporary foster care, veterinary access/zoonotic safety) for keeping people and their companion animals together during such difficult times. Originality/value This article is unique in that it delineates the animal companionship benefits in terms of how such may help alleviate stressors associated with a pandemic.